2004
DOI: 10.1016/j.jsgi.2003.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hypoxia Alters Endocrine and Physiologic Responses to Umbilical Cord Occlusion in the Ovine Fetus

Abstract: Despite similar ACTH responses to UCO, the cortisol response was greater in the LTH fetuses than in normoxic controls. LTH appears to result in enhanced adrenal sensitivity to a secondary stressor or altered cortisol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(88 citation statements)
references
References 34 publications
7
80
1
Order By: Relevance
“…This initial bradycardia is thought to represent a chemoreceptor response that is vagally mediated (Bartelds et al, 1993). Consistent with our data, in chronically hypoxic high altitude-exposed fetal sheep with a comparable reduction in fetal arterial pO 2 and without acidosis, the bradycardic response to umbilical cord occlusion was shown not to be affected (Imamura et al, 2004). As reported by others for partial cord occlusions (Giussani et al, 1997), we observed that following the initial bradycardia fetal heart rate stabilized or even increased slightly only to fall again during the last minute of occlusion.…”
Section: Discussionsupporting
confidence: 90%
“…This initial bradycardia is thought to represent a chemoreceptor response that is vagally mediated (Bartelds et al, 1993). Consistent with our data, in chronically hypoxic high altitude-exposed fetal sheep with a comparable reduction in fetal arterial pO 2 and without acidosis, the bradycardic response to umbilical cord occlusion was shown not to be affected (Imamura et al, 2004). As reported by others for partial cord occlusions (Giussani et al, 1997), we observed that following the initial bradycardia fetal heart rate stabilized or even increased slightly only to fall again during the last minute of occlusion.…”
Section: Discussionsupporting
confidence: 90%
“…Although we previously reported that basal plasma levels of cortisol are not different between LTH and control fetuses (1,23), the potential does exist for lower intra-adrenal concentrations of cortisol in the LTH fetus, as we previously found that the enzymes responsible for cortisol synthesis are lower in the cortex of LTH fetuses (33). It also remained possible that expression of the GR was suppressed in the medulla of the LTH adrenal, thus decreasing the sensitivity to cortisol.…”
Section: Discussionmentioning
confidence: 76%
“…After spending ϳ105-110 days of gestation at high altitude, the animals were transported to Loma Linda University Medical Center Animal Research Facility (elevation: 346 m), where they were implanted with a nonocclusive tracheal catheter (4.0 mm OD) and an arterial catheter. Maternal PO 2 for LTH group was maintained at ϳ60 mmHg (mean PO2 measured in animals at altitude) by adjusting humidified nitrogen (N2) gas flow through the tracheal catheter as previously described (1,21,23). Normoxic, age-matched pregnant ewes were used as controls.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would exert an inhibitory effect on basal cortisol production overcoming the low level of stimulation by elevated basal ACTH. Stimulation with high levels of ACTH in vitro (Monau et al 2010) or those observed in vivo in response to a secondary stressor (Adachi et al 2004, Imamura et al 2004 would decrease NO activity, thus enhancing cortisol output. We propose that this can occur through ACTH interaction with the MEK/ERK1/2 and/or the AKT/IP 3 .…”
Section: Potential Indirect Effects On Nomentioning
confidence: 99%